Comparative response to PDT with methyl-aminolevulinate and temoporfin in cutaneous and oral squamous cell carcinoma cells - J. Nicolás-Morala; M. Alonso-Juarranz; A. Barahona; S. Terrén; S. Cabezas; F. Falahat; Y. Gilaberte; S. Gonzalez; A. Juarranz; M. Mascaraque (Scientific Reports, 2024)
Abstract Cutaneous and Head and Neck squamous cell carcinoma (CSCC, HNSCC) are among the most prevalent cancers. Both types of cancer can be treated with photodynamic therapy (PDT) by using the photosensitizer Temoporfin in HNSCC and the prodrug methyl-aminolevulinate (MAL) in CSCC. However, PDT is not always effective. Therefore, it is mandatory to correctly approach the therapy according to the characteristics of the tumour cells. For this reason, we have used cell lines of CSCC (A431 and SCC13) and HNSCC (HN5 and SCC9). The results obtained indicated that the better response to MAL-PDT was related to its localization in the plasma membrane (A431 and HN5 cells). However, with Temoporfin all cell lines showed lysosome localization, even the most sensitive ones (HN5). The expression of mesenchymal markers and migratory capacity was greater in HNSCC lines compared to CSCC, but no correlation with PDT response was observed. The translocation to the nucleus of β-catenin and GSK3β and the activation of NF-κβ is related to the poor response to PDT in the HNSCC lines. Therefore, we propose that intracellular localization of GSK3β could be a good marker of response to PDT in HNSCC. Although the molecular mechanism of response to PDT needs further elucidation, this work shows that the most MAL-resistant line of CSCC is more sensitive to Temoporfin.